Visitors’ awareness on safety measurements at Penang Botanical Garden (PBG), Malaysia - Lee, Lin Wei (2018)
The study was conducted in Penang Botanical Garden (PBG) because of the natural hazards that threaten visitors’ recreational safety. Visitors need to be aware about the natural environment when doing outdoor recreation activities. The purpose of the study was to measure visitors’ level of awareness towards recreational safety and determine the factors influencing visitors’ awareness on safety measurements. A total of 250 respondents participated in the questionnaire survey. The study utilized questionnaire to measure visitors’ awareness on safety measurements at PBG. Results indicated that the visitors were moderately aware with the overall safety measurements with the mean value of 2.86 out of 5.00. The highest mean score was at 3.16 obtained for the general signboard “Do not feed the monkeys”. The lowest mean score was at 2.40 obtained for the statement “Appear of wild boars in the park” from the attribute of wildlife attack. Multiple regression analysis showed that the number of visits, accompaniment, duration spend in the garden, sources of information about PBG, education level and monthly salary influenced visitors’ awareness on safety measurements.